EDUKASI PENCEGAHAN KEKERASAN BERBASIS GENDER ONLINE MELALUI VIDEO ANIMASI - Alila Pramiyanti; Anggian L. Pasaribu (KRIDA CENDEKIA, 2025)
The internet and social media can be a means for the emergence of acts of violence and exploitation, especially against women and children. The number of cases of Online Gender- Based Violence (KBGO) has increased over time. Although the KPPPA has emphasized the importance of early sexual education, challenges in the form of discomfort and taboos still need to be overcome. The topic of sexuality is still considered taboo in many circles of Indonesian society. In addition, limited access to accurate and comprehensive information and resources about the dangers of Online Gender-Based Violence (KBGO) is also an obstacle. Various efforts are still needed to educate the public, provide appropriate materials, and train educators are essential to ensure that Indonesian children and adolescents get the protection they need from Online Gender-Based Violence (KBGO) and other forms of sexual violence. Therefore, the community service team will produce an educational video on preventing Online Gender-Based Violence (KBGO) for the community under the Pasupati Bridge, which is part of the Taman Sari Village, East Bandung. The provincial and city governments are currently revitalizing the area under the Pasupati Bridge. This revitalization is part of an effort to increase friendly and inclusive public spaces. Through educational videos on preventing KBGO, teenagers under the Pasupati bridge will gain a better understanding of and appreciation for the importance of preventing KBGO, thereby supporting friendly and inclusive public spaces